Perceived quality of health care in macular disease: a survey of members of the Macular Disease Society. Issue 7 (1st July 2002) - Mitchell, J; Bradley, P; Anderson, S J; ffytche, T; Bradley, C
Abstract : Aim: To investigate the experiences of people with macular disease within the British healthcare system. Method: The Macular Disease Society Questionnaire, a self completion questionnaire designed to survey the experiences of people with macular disease, was sent to 2000 randomly selected members of the Macular Disease Society. The questionnaire incorporated items about people's experiences with health professionals and the information and support provided by them at the time of diagnosis and thereafter. Results: Over 50% thought their consultant eye specialist was not interested in them as a person and 40% were dissatisfied with their diagnostic consultation. 185 people thought their general practitioner (GP) was well informed about macular disease but twice as many people thought their GP was not well informed. About an equal number of people thought their GP was supportive as those who thought their GP was not supportive. A total of 1247 people were told "nothing can be done to help with your macular disease." A number of negative emotional reactions were experienced by those people as a result, with 61% of them reporting feeling anxious or depressed. Of 282 people experiencing visual hallucinations after diagnosis with macular disease, only 20.9% were offered explanations for them. Conclusions: Many people with macular disease have unsatisfactory experiences of the healthcare system. Many of the reasons for dissatisfaction could be resolved by healthcare professionals if they were better informed about macular disease and had a better understanding of and empathy with patients' experiences.